Dynamics of the alpine timberline and its response to climate change in the Hengduan mountains over the period 1985–2015 - Lei Tian; Wenxue Fu; Yu Tao; Mingyang Li; Lei Wang (Ecological Indicators, 2022)
The spatiotemporal change in the alpine timberline, an ecosystem ecotone, is an ideal indicator for use in climate change research. In order to gain a quantitative understanding of the response of the alpine timberline to climate change, the Hengduan Mountains region of China was selected as a study area and a series of 136 Landsat images covering this area that were acquired in 1985, 1995, 2005 and 2015 were collected. First, the alpine timberline was retrieved and the spatiotemporal dynamics of the timberline were explored. The effect of topography on the location of the alpine timberline was also analyzed. The results indicate that the average elevation of the timberline increased by about 55 (±8.54) m from 3992.58 m in 1985 to 4047.60 m in 2015; however, there was obvious spatial heterogeneity in these changes. On the whole, the average elevation of the timberline on shaded slopes (northern, northeastern, and northwestern slopes) were found to be about 160 m higher than on sunward slopes (southern, southeastern, and southwestern slopes). It was also found that, over the period 1985–2015, there has been an obvious acceleration in the upward tendency of the alpine timberline. Finally, the climate variables that are driving this timberline shift were identified and evaluated using the partial least squares (PLS) regression method. The results indicate that the average annual temperature (TEM_Year), total precipitation during the growing season (PRE_Grow), and growing season temperature (TEM_Grow) were the significant positive factors driving the rise in the timberline elevation; the total annual precipitation (PRE_Year) was found to have an unexpected negative influence. Besides, other climatic factors (e.g., strong winds) and non-climate variables (e.g., human influence and soil properties) should be also included in future related studies to enhance the understanding of the link between forest vegetation and climate change under extreme conditions.